My best mathematical and logic puzzles - Gardner, Martin (New York : Dover publications, 1994)
Noted expert selects 70 "short" puzzles. The Returning Explorer, The Mutilated Chessboard, Scrambled Box Tops, and 67 more. Solutions included
Keywords: Mathematical recreations; Logic puzzles